Easy to learn, difficult to master : Pong, Atari, and the dawn of the video game - Kushner, David, 1968- (Bold Type Books, 2022)
"A deep, nostalgic dive into the advent of gaming, Easy to Learn, Difficult to Master returns us to the emerging culture of Silicon Valley. At the center of this graphic history, dynamically drawn in colors inspired by old computer screens, is the epic feud that rages between Atari founder Nolan Bushnell and inventor Ralph Baer for the title of "father of the video game." While Baer, a Jewish immigrant whose family fled Germany for America, developed the first TV video-game console and ping-pong game in the 1960s, Bushnell, a self-taught whiz kid from Utah, put out Atari's pioneering table-tennis arcade game, Pong, in 1972. Thus, a prolonged battle began over who truly spearheaded the multibillion-dollar gaming industry, and around it a sweeping narrative about invention, inspiration, and the seeds of digital revolution"--Back cover.